A network-independent tool-based usable authentication system for Internet of Things devices. Issue 108 (September 2021) - Jung, Changhun; Choi, Jinchun; Jang, Rhongho; Mohaisen, David; Nyang, DaeHun
Abstract: In this paper, we introduce a hardware-based system with a protocol realization to authenticate Internet of Things (IoT) devices. DigitalSeal is a novel standalone network-independent authentication tool implemented using an Arduino UNO and various components. DigitalSeal 's I/O elements read a barcode and display a barcode data and its corresponding HMAC, which are used for authentication. DigitalSeal can manage cryptographic keys securely and provide a data integrity in order to defend against Man-in-the-Middle (MitM) and Man-in-the-Browser (MitB) attacks. Moreover, DigitalSeal can be used in various applications, such as an authentication system or protocol, an online/offline transaction, a login session, and an IoT device authentication. Using DigitalSeal, we propose a new protocol for IoT device authentication, providing various security benefits and reducing the burden of key maintenance for a large number of IoT devices. Our authentication protocol realization with DigitalSeal provides a convenient method for securely managing password for multiple IoT devices, prevents unauthorized IoT devices from connecting to the user's gateway (an IoT home/enterprise network), and secures the communication between the IoT device and the gateway. Our system and associated protocol are both cost-effective and usable. According to our experiments, most users are able to obtain the authentication credential (the HMAC) within 3 seconds with more than 93% accuracy using DigitalSeal.